ENGLISH MODAL VERBS IN MODAL VERB PHRASE STRUCTURES AND LEXICAL RESOURCE OF MODALITY (Proceedings of International Educators Conference, 2023)
This article considers some aspects of a semantic analysis of the English Modal Auxiliaries and their both the epistemic and the deontic characteristics of modality, being expressed them in Modal verb phrase structures.